2015
DOI: 10.1016/s0140-6736(15)00131-2
|View full text |Cite|
|
Sign up to set email alerts
|

Screening for fetal growth restriction with universal third trimester ultrasonography in nulliparous women in the Pregnancy Outcome Prediction (POP) study: a prospective cohort study

Abstract: SummaryBackgroundFetal growth restriction is a major determinant of adverse perinatal outcome. Screening procedures for fetal growth restriction need to identify small babies and then differentiate between those that are healthy and those that are pathologically small. We sought to determine the diagnostic effectiveness of universal ultrasonic fetal biometry in the third trimester as a screening test for small-for-gestational-age (SGA) infants, and whether the risk of morbidity associated with being small diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
605
7
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 512 publications
(692 citation statements)
references
References 27 publications
(39 reference statements)
33
605
7
13
Order By: Relevance
“…The Pregnancy Outcome Prediction study was conducted at the Rosie Hospital, Cambridge, U.K., and has previously been described in detail (9,10). In brief, it was a prospective cohort study of nulliparous women with a viable singleton pregnancy who attended the hospital for their dating ultrasound scan between 14 August 2008 and 31 July 2012.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pregnancy Outcome Prediction study was conducted at the Rosie Hospital, Cambridge, U.K., and has previously been described in detail (9,10). In brief, it was a prospective cohort study of nulliparous women with a viable singleton pregnancy who attended the hospital for their dating ultrasound scan between 14 August 2008 and 31 July 2012.…”
Section: Designmentioning
confidence: 99%
“…The conduct and descriptive data of the research ultrasounds have previously been described in detail (9,10). In brief, gestational dating was performed using ultrasound, and 99.5% of these examinations were performed prior to 15 wkGA.…”
Section: Analysis Of Fetal Growthmentioning
confidence: 99%
“…De Jong showed in 1999 that the fetal growth rate was significantly lower in pregnancies that had operative delivery for presumed fetal distress (20.9 g/day) or neonatal unit admission (20.3 g/day) compared to those with uncomplicated outcome (21.9 g/day) [29]. A large screening study of 4,512 nulliparous woman recruited over a four year period in Cambridge UK [30] found that an EFW below the 10 th centile was associated with an increased risk of neonatal morbidity, but only if the fetal AC growth velocity was in the lowest decile (relative risk of 17.6). In 2008, Eixarch showed that only fetuses with signs of cerebral redistribution, identified as those with a low middle cerebral artery (MCA) pulsatility index (PI), suffered from lower communication and problem solving scores in childhood [31].…”
Section: Assessment Of Fetal Growth At Termmentioning
confidence: 99%
“…It is notable that the improvement of the detection of SGA neonates using assessment of the fetal growth (biometry) was associated with a high false positive rate (two false positives for each additional SGA neonate detected), as shown in the Cambridge screening study [30]. It is clear, therefore, that additional parameters such as fetal Doppler or biochemical markers, such as placental growth factor, are required to optimize the identification of fetuses at risk of adverse outcome [30,32].…”
Section: Assessment Of Fetal Growth At Termmentioning
confidence: 99%
See 1 more Smart Citation